Aerobic Mesophilic Bacteria and Sensory Qualities of Yellow Alkaline Noodles during Storage - Abd Ghaffar, Siti Suwaibah (2008)
A study was conducted to evaluate the aerobic mesophilic bacteria and sensory characteristics of yellow alkaline noodles (YAN) during storage. Samples were obtained from 9 commercial noodles processing plants, 3 from each category which were situated in Selangor and Kuala Lumpur. The categories of processing plants were determined according to the processing methods employed namely; automated processing method (AP samples); semi automated processing method (SM samples) and manual processing method (MP samples). The samples were collected on the day of production, placed in a polystyrene box and transported to the laboratory where they were stored at ambient temperature (28 ± 2 ºC). Aerobic mesophilic counts (APC), pH and sensory evaluation of noodle samples were analysed daily for 9 days. APC in all samples increased significantly (P<0.05) from around log 3 CFU/g to around log 7 CFU/g during storage. The pH of all samples decreased significantly (P<0.05) from initial pH around 10 to 6 at end of storage. Sensory attributes to evaluate YAN spoilage characteristics include; off odours, firmness, elasticity and sliminess. Samples began to deteriorate and became unacceptable to panelist around day 2-3 days of storage. Composition of aerobic mesophilic bacteria were identified using the Biolog Microstation System with its equivalent software and database. A total of 90 isolates, were isolated and the pre-dominant bacteria identified include Staphylococcus sciuri and Ochrobactrum anthropi which were common in all samples and Alcaligenes faecalis which was only isolated from SP and MP samples. Another study was conducted to evaluate the growth profile of pre-dominant bacteria in YAN. Samples were treated with solutions of S. sciuri (SS), A. faecalis (AF) and O. anthropi (OA) at level of log 5-6 CFU/g. Samples were stored at ambient temperature (28 ± 2 ºC) and analysed daily for aerobic mesophilic counts (APC), pH and sensory evaluation for 4 days. APC of SS and AF samples increased significantly (P>0.05) during storage and more rapidly compared to OA samples. The pH values of SS and AF samples decreased significantly (P>0.05) than OA samples during storage. Panelist associated development of off odours in SS and AF samples with off odours of samples produced from commercial processing plants. Volatiles compounds produced by S. sciuri and A. faecalis were accomplished using SPME-GCMS method. Identification in the volatiles compounds in SS and AF samples were from alcohol groups and disulfide, dimethyl. A different study was conducted to evaluate aerobic mesophilic bacteria and sensory charactheristics of YAN treated with lactic acid and nisin. Untreated samples were regarded as control and samples treated with boric acid were analysed as comparison due to its abuse usage in YAN. Noodle samples were treated by dipping in 0.5%, 1.0% or 1.5% solution of lactic acid (v/v), nisin (w/v) or boric acid (w/v) for 30 seconds. Samples were stored at ambient temperature (28 ± 2 ºC). Duplicate analyses of APC, pH, and sensory evaluation were conducted on day 0, 1, 3, 5, 7, and 10 of storage. A total of 200 isolates were isolated from noodle samples during storage and further characterized using series of biochemical tests. APC of all samples increased significantly (P<0.05) from log 2.42 CFU/g for control (untreated) samples and around log 3-4 CFU/g for treated sampled to around log 10 CFU/g at end of storage. pH of all samples decreased significantly (P<0.05) throughout storage period. Sensory evaluation showed that samples treated with lactic acid, nisin and boric acid were rejected by panelist due to unacceptable odour and texture. Results showed that the ability of nisin, lactic acid and boric acid to reduce microbial load in noodle samples were not significant due to the fact that the inhibitory effect were limited to certain group of bacteria only. The potential of lactic acid and nisin acting singly to inhibit growth of aerobic mesophilic bacteria in YAN were not significant however the enhancement on its potential may probably be achieved by acting in combinations or with other preservatives.